2013
DOI: 10.14233/ajchem.2013.15836
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Determination of Aflatoxins in Wheat Grains Collected from Central Areas of the Punjab, Pakistan

Abstract: Food is one of the most intimate and important components of our chemical environments. Good food is not only expected to look fresh and tasty but it must be free from all contaminants. Mycotoxins are natural food and feed contaminants mainly produced by moulds of genera Aspergillus flavus, Aspergillus paraciticus, Aspergillus nomius 1 . Mycotoxin contaminated food consumption is associated with several cases of human poisoning or mycotoxicosis and some times resulting in death 2 . Fungus invades, most commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…However, in the present investigation, aflatoxin content in maize ranged from < LOD to 168.2 µg kg −1 with average values of 29.1, 36.9 and 102.2 µg kg −1 for the southern irrigated zone, northern irrigated zone and arid (rain-fed) zone, respectively. These results were in close agreement with those of Ahsan et al (2010) and Khatoon et al (2012). According to Grybauskas et al (2000), maize containing 20 µg kg −1 aflatoxin or more should not be sold commercially and not be milled for human consumption.…”
Section: Aflatoxinsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the present investigation, aflatoxin content in maize ranged from < LOD to 168.2 µg kg −1 with average values of 29.1, 36.9 and 102.2 µg kg −1 for the southern irrigated zone, northern irrigated zone and arid (rain-fed) zone, respectively. These results were in close agreement with those of Ahsan et al (2010) and Khatoon et al (2012). According to Grybauskas et al (2000), maize containing 20 µg kg −1 aflatoxin or more should not be sold commercially and not be milled for human consumption.…”
Section: Aflatoxinsupporting
confidence: 93%
“…Moulds are distributed widely as environmental contaminants and under favourable conditions of temperature and humidity, grow on commodities like maize (Brera et al 1998) and produce mycotoxins. In Pakistan, few studies have reported on mycotoxin contamination in local varieties of maize during the last three years (Ahsan et al 2010;Shah et al 2010;Ishrat et al 2012;Khatoon et al 2012). Furthermore, recent domestic surveys report the presence of mycotoxins in chillies (Iqbal et al 2009) fruits and vegetables (Sahar et al 2009) and poultry feed (Saleemi et al 2010;Anjum et al 2011;Rashid et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Maize is found to be a favorable substrate for fungal growth and mycotoxin formation (Nesci and others ; Trung and others ). The warm and humid conditions of Pakistan are suitable for fungal infection and toxigenesis during growth, harvesting, processing, and storage of maize (Ahsan and others ). A variety of fungi, including A. parasiticus, A. flavus, F. proliferatum, F. verticillioides , and P. verrucosum can damage maize (Cardwell and others ; Abbas and others ).…”
Section: Mycotoxin Contamination Of Food and Feed In Pakistanmentioning
confidence: 99%
“…In Pakistan, mycotoxin occurrence in maize is reported from mainly Punjab and KP provinces. Maize grain samples from Punjab (Faisalabad) were analyzed for aflatoxin presence by reverse‐phase high‐performance liquid chromatography (RP‐HPLC) (Ahsan and others ). Aflatoxin contamination (up to 62 μg/kg) was found in 34 out of 40 samples, with highest levels in samples collected from rural areas (90%) and some of the samples exceeded the permissible limits established by EU.…”
Section: Mycotoxin Contamination Of Food and Feed In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation